Ombudsman Dalam Peningkatan Transparansi dan Akuntabilitas Pelayanan Publik - Yuswarni Yuswarni; Diemyati Soedja; Silvia Balqis; Arizal Arizal (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2024)
This study discusses how the ombudsman increases transparency and accountability of public services, where the ombudsman is an institution that has the authority to oversee the implementation of public services organized by the government of State Enterprises, Regions, Private Bodies, or individuals given the task of organizing public services where the budget in its implementation comes from state finances, This research uses a qualitative method where data sources are obtained from literature sources (Literature Study) where the data obtained is analyzed and summarized and written descriptively, so that the results obtained that what the ombudsman does in increasing transparency and accountability of public services is to improve the quality of settlement of public reports, Increase Access to Public Service Complaints, Prevention of Maladministration, Acceleration and Organizational Transformation and Efforts to Expand Cooperation. The activities carried out are efforts to make public services better, transparent, and accountable. Accountable and in the last five years, public participation has increased, this indicates that the increase, this indicates that that the ombudsman institution has the trust of the community to solve public service problems and can solve public service problems and can affect changes in public services from the recommendations of the results of the Ombudsman examination. Public services from the recommendations of the results of the Ombudsman examination, but the first concern is how the ombudsman can be strengthened with the need for strengthened by the need for sanctions, where sanctions are needed to increase compliance of public institutions to implement to increase the compliance of public institutions in order to implement all the results of the ombudsman examination, both in corrective actions and recommendations. Secondly, there needs to be protection and security for victims or whistleblowers so that they can be protected from potential threats. Protection and security for victims or whistleblowers so that they can be protected from potential threats both from physical and administrative threats that can be or administrative threats that can have an impact on careers, jobs and businesses.